2018
DOI: 10.1002/hec.3645
|View full text |Cite
|
Sign up to set email alerts
|

Information, education, and health behaviors: Evidence from the MMR vaccine autism controversy

Abstract: In the wake of strong, although later refuted, claims of a link between autism and the measles-mumps-rubella (MMR) vaccine, I examine whether fewer parents immunized or delayed vaccinations for their children and if there was a differential response by mother's education level. Using various controls and a differencing strategy that compares in MMR take-up with other vaccines, I find that the MMR-autism controversy led to a decline in the immediate years and that there were negative spillovers onto other vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 59 publications
(82 reference statements)
7
35
0
Order By: Relevance
“…The consequences of this failed debunking turned out to be rather severe: The controversy led to a decrease in MMR vaccine uptake and, in turn, to an increase in mumps and measles infections, leading to preventable diseases and deaths (Hargreaves, Lewis, & Speers, 2003;Nyhan, Reifler, Richey, & Freed, 2014;Poland & Spier, 2010). Studies also revealed negative spillovers onto other vaccines (Chang, 2018). The case impressively shows the fatal consequences when misinformation spreads and also illustrates the "societal cost of misinformation": the money spent on follow-up studies and information campaigns to debunk information that is factually incorrect (Lewandowsky et al, 2012, p. 107).…”
Section: Ex Post Debunking Via Correctionsmentioning
confidence: 99%
“…The consequences of this failed debunking turned out to be rather severe: The controversy led to a decrease in MMR vaccine uptake and, in turn, to an increase in mumps and measles infections, leading to preventable diseases and deaths (Hargreaves, Lewis, & Speers, 2003;Nyhan, Reifler, Richey, & Freed, 2014;Poland & Spier, 2010). Studies also revealed negative spillovers onto other vaccines (Chang, 2018). The case impressively shows the fatal consequences when misinformation spreads and also illustrates the "societal cost of misinformation": the money spent on follow-up studies and information campaigns to debunk information that is factually incorrect (Lewandowsky et al, 2012, p. 107).…”
Section: Ex Post Debunking Via Correctionsmentioning
confidence: 99%
“…Similarly, Smith, Ellenberg, Bell, and Rubin (2008) examined MMR uptake and nonreceipt in the United States and found declines in 1999 and 2000 and then a return to previous levels of vaccination. More recently, Chang (2018) showed that controversy led to a decline in MMR immunization rates and negative spillovers onto the use of other vaccines in the United States. This paper complements these existing studies in two important ways.…”
mentioning
confidence: 99%
“…Other than socio-cultural and domestic context, income and education also play a large role in access and attitudes: recall the broad conclusions of Sandford et al [37], Haider et al [35], Hungerford et al [32], and Baker et al [33], that socioeconomic deprivation is positively correlated with reduced uptake and timeliness of MMR vaccination. Haider et al [35] notes that this, remarkably, is a reverse of the pattern that was well documented in the 2000s; in comparable studies conducted at the height of the Wakefield controversy, affluent groups were the least likely to vaccinate and had seen the fastest reductions in uptake [72].…”
Section: Socioeconomic Variables Mediate Every Stage Of Vaccinationmentioning
confidence: 91%